2011
DOI: 10.1644/10-mamm-a-252.1
|View full text |Cite
|
Sign up to set email alerts
|

DNA-based approach to aging martens (Martes americanaandM. caurina)

Abstract: Demographic structure is central to understanding the dynamics of animal populations. However, determining the age of free-ranging mammals is difficult, and currently impossible when sampling with noninvasive, genetic-based approaches. We present a method to estimate age class by combining measures of telomere lengths with other biologically meaningful covariates in a Bayesian network. We applied this approach to American and Pacific martens (Martes americana and M. caurina) and compared predicted age with tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Age determination would result in more accurate density estimates and the ability to identify population size of independently aged animals. Similar work in aging animals based on DNA telomere length has been done with American and Pacific martens (Martes americana and M. caurina; Pauli et al 2011). Given the small study area size relative to a cougar's home range, transients were likely available for capture.…”
Section: Discussionmentioning
confidence: 97%
“…Age determination would result in more accurate density estimates and the ability to identify population size of independently aged animals. Similar work in aging animals based on DNA telomere length has been done with American and Pacific martens (Martes americana and M. caurina; Pauli et al 2011). Given the small study area size relative to a cougar's home range, transients were likely available for capture.…”
Section: Discussionmentioning
confidence: 97%
“…Telomere degradation occurs when cells divide, and loss rates are accelerated by DNA damage, especially oxidative damage (von Zgli-nicki 2002, Monaghan 2014. Traditionally, telomeres are associated with the biology of aging (Holmes andMartin 2009, Dunshea et al 2011) and have been shown to shorten with age in many species (Haussmann and Vleck 2002, Haussmann et al 2003, Pauli et al 2011, Mü ezzinler et al 2013, but see (Francis et al 2006). However, in long-lived birds a large telomere loss with chronological age is not the norm (Hall et al 2004, Foote et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Remotely collected genetic information has been used in other animals to examine population structure and movements (Baker et al 1993, Witteveen et al 2009), examine genetic diversity (Schmidt et al 2009), determine sex ratios (Curtis et al 2007), and estimate abundance (Palsbøll et al 1997, Woods et al 1999. Other studies have used remote biopsy darts to collect tissues to test for contaminants (Ross et al 2000, Wiig et al 2000, conduct stable isotope and fatty acid analyses (Hooker et al 2001, Witteveen et al 2009), and estimate individual ages (Herman et al 2008(Herman et al , 2009Pauli et al 2011).…”
mentioning
confidence: 99%